E-waste for health: recycling smartphones for health monitoring - Costa, Leandro Augusto de Almeida; Furtado, Brena Ataíde; Almeida, Edilson Brabo; Callegari, Bianca; Crisp, Alex Harley; Chaves, Rafael Oliveira; Pinheiro, Maria da Conceição Nascimento; Souza, Givago Silva (Frontiers in Digital Health, 2025)
Portable digital electronic devices have been widely used around the world for different everyday tasks. However, every day there is also an increasing dumping of these electronic devices, especially smartphones, creating a public health problem called electronic waste or e-waste. This Viewpoint discusses how e-waste could be used by governments to promote digital health policies, especially in poorer countries. The use of e-waste could lower health care costs and reduce exposure to the metals contained in these materials.